Dufour-Soret Effects on 3D Convective Viscoelastic Fluid Flow Upon a Stretched Surface - Bhuvaneswari, M.; Sivasankaran, S.; Karthikeyan, S.; Rajan, S. (International Journal of Engineering and Technology, 2018)
The purpose of this analytical work is to investigate the Dufour-Soret effects on three dimensional unsteady boundary layer flows, mass and heat transfer of a viscoelastic fluid upon a stretched surface in the existence of internal heat generation/absorption. The equations governing the flow are converted using similarity variables into a set of non-linear ordinary differential equations. The series solution is obtained by homotopy analysis. The results are analyzed for the influences of the various pertinent constants involving in the study. The mass and heat transfer rates are calculated by the localized Sherwood and Nusselt numbers along the surface.Â Â